2020
DOI: 10.1038/s41415-020-2112-7
|View full text |Cite|
|
Sign up to set email alerts
|

The efficacy of an extraoral scavenging device on reduction of splatter contamination during dental aerosol generating procedures: an exploratory study

Abstract: Introduction This study was conducted in light of the SARS-CoV-2 pandemic, which brought UK dentistry to a standstill. The market has seen a recent influx of unproven extraoral scavengers (EOSs), which claim to reduce the risk of particulate spread. Aims To investigate the efficacy of a commercially available EOS device on contamination reduction during dental aerosol generating procedures (AGPs). The secondary aim was to investigate differences between open and closed dental operatories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
49
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 17 publications
8
49
1
1
Order By: Relevance
“…Previous recommendations that bay partitions should have a height of 2 m above the patient are therefore likely to be unnecessary [ 9 ]. These findings are also in keeping with a recent study reporting splatter analysis from visual analysis of litmus paper when citric acid was added to the irrigation system [ 42 ]. The authors reported a similar distribution pattern of splatter up to 1.33 m. This study, however, only analysed splatter in single repetitions, and did not report the level of suction used.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous recommendations that bay partitions should have a height of 2 m above the patient are therefore likely to be unnecessary [ 9 ]. These findings are also in keeping with a recent study reporting splatter analysis from visual analysis of litmus paper when citric acid was added to the irrigation system [ 42 ]. The authors reported a similar distribution pattern of splatter up to 1.33 m. This study, however, only analysed splatter in single repetitions, and did not report the level of suction used.…”
Section: Discussionsupporting
confidence: 90%
“…We assessed the impact of two levels of dental suction within this study: medium volume suction (159 L/min air) and low volume suction (40 L/min air) as defined by current standards [ 43 ]. It is worth noting many previous studies using ‘high volume dental suction’ did not report their suction level [ 20 , 28 , 42 ] or used suction that fell below the 250 L/min criteria for high volume aspiration [ 31 ]. Reassuringly, we observed little difference in the reductions of close and distant contamination between low and medium suction, perhaps indicating that there is quite a low threshold for suction exerting substantial benefit.…”
Section: Discussionmentioning
confidence: 99%
“…There is a serious deficiency in the literature regarding the risks posed by aerosols and splatter from aerosol-generating procedures (AGPs) in dental settings and the efficacy of various aerosol mitigation techniques. A number of studies have collected aerosols and splatters directly onto a collecting surface for subsequent analysis, which include fluorescent [13][14][15][16][17] or non-fluorescent [18][19][20] based chromatic indicators and microbiological methods using culture media [21][22][23][24] . These studies are limited by their inefficient collection of small size aerosols (<~50 µm) which do not provide a comprehensive characterization over the entire size spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has the potential to spread during dental procedures through a number of routes. Attention has focused on the spread via droplets or ‘splatter’ that can either impact directly on the face of a susceptible person or, be deposited on a surface (Shahdad et al 2020; Allison et al 2021). However, there is increasing evidence that aerosols, particularly when highly concentrated in enclosed environments, may play an important role in disease transmission (WHO 2020; Li et al 2020; Miller et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have added dye or fluorescent marker to the water lines to examine the distribution of splatter and detect deposits as small as 1000 μm 2 in area, although this dimension exceeds what is typically classed as an aerosol (Chiramana et al 2013; Veena et al 2015; Shahdad et al 2020; Allison et al 2021). Small particles (≤16 – 27μm) deposited on microscope slides have also been studied, however, this did not account for aerosols that did not settle during the experiment (Junevicius et al 2005).…”
Section: Introductionmentioning
confidence: 99%